Peningkatan Kesadaran Pola Hidup Sehat melalui Kampanye Persuasif Jus Detoks bagi Mahasiswa dan Dosen - Ananda Fortunisa; Wapa Wapiah (Indonesian Journal for Social Responsibility, 2026)
An unbalanced diet and low consumption of fruits and vegetables are part of an unhealthy lifestyle that increases the risk of non-communicable diseases among students and lecturers. To raise awareness of the importance of healthy eating, this community service activity was carried out through a detox juice campaign based on persuasive communication. The method used was Participatory Action Research (PAR), with a pretest and posttest evaluation approach involving fifty students and three lecturers. The campaign lasted for three days and involved the distribution of fruit and vegetable juices, direct education, and the dissemination of information through social media and printed materials. The results showed a significant improvement in the participants' attitudes and perceptions, which were measured using pretest and posttest questionnaires on awareness, attitudes, and behavioral intentions regarding detox juice consumption and the benefits of eating vegetables and fruit. Some participants also reported improvements in body freshness and digestion. Thus, the persuasive communication-based detox juice campaign was effective in increasing awareness and intention to consume healthy foods, and has the potential to be developed in similar activities with a wider scope.